Hormonal Contraception and Menstrual Cycle Control at High Altitude: A Scoping Review-UIAA Medical Commission Recommendations - Horakova, Lenka; Kriemler, Susi; Študent, Vladimír; Pichler Hefti, Jacqueline; Hillebrandt, David; Jean, Dominique; Mateikaitė-Pipirienė, Kastė; Paal, Peter; Rosier, Alison; Andjelkovic, Marija; Beidlemann, Beth; Derstine, Mia; et al. (High altitude medicine & biology, 2024)
Horakova, Lenka, Susi Kriemler, Vladimír Študent, Jacqueline Pichler Hefti, David Hillebrandt, Dominique Jean, Kastė Mateikaitė-Pipirienė, Peter Paal, Alison Rosier, Marija Andjelkovic, Beth Beidlemann, Mia Derstine, and Linda E. Keyes. Hormonal contraception and menstrual cycle control at high altitude: a scoping review-UIAA Medical Commission recommendations. High Alt Med Biol. 25:255-265, 2024. Background: Women who use hormonal contraception (HC) may have questions about their use during travel to high altitude. This scoping review summarizes current evidence on the efficacy and safety of HC and cycle control during high-altitude travel. Methods: We performed a scoping review for the International Climbing and Mountaineering Federation (UIAA) Medical Commission series on Women's Health in the Mountains. Pertinent literature from PubMed and Cochrane was identified by keyword search combinations (including contraception) with additional publications found by hand search. Results: We identified 17 studies from 7,165 potentially eligible articles. No articles assessed the efficacy of contraception during a short-term high-altitude sojourn. Current data show no advantage or disadvantage in HC users for acclimatization or acute mountain sickness (AMS). Use of HC during high-altitude travel is common and safe for menses suppression. A potential concern of estrogen-containing HC is the increased thrombotic risk, which theoretically could be compounded in hypobaric hypoxia. Conclusions: Evidence is limited for the interaction of HC and high altitude on performance, thrombosis, and contraceptive efficacy. HC does not affect the risk of AMS. The most efficacious and safest method at high altitude is generally the one women are most familiar with and already using.
Keywords: Menstrual Cycle; Female; horolezectví; lidé; nadmořská výška; Altitude; hormonální antikoncepce; ženské pohlaví; menstruační cyklus; Humans; Mountaineering; Hormonal Contraception